(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The proposed and developed methodology is designed to determine the indicators of reliability and operability of disposable chemical power sources. It is recommended for conducting tests of physical samples (real models) under various environmental impacts, under mechanical-dynamic loads, as well as in various operating conditions. The methodology includes subjecting the samples to testing the impact of destabilizing factors of the environment in order to determine their workability and reliability. Conducting this independent test is required due to the importance of the power source and in order to obtain sufficient statistical information about the reliability of its electrochemical elements. To ensure the completeness and comprehensiveness of the study, an additional methodology has been compiled – Methodology for Identification of Physical Models of a Power Source.